Examining the implmentation of situational Language teaching (SLT) in the EFL classroom: A semi-systematic literature review - Arcos Hermosa, Mayra Elizabeth (2025)
Situational Language Teaching (SLT) is well-known for its practical applications in second language teaching and learning, as it emphasizes the use of real-life situations and contexts. SLT has significantly influenced lear-ners’ language skills since its inception. The need to analyze the implementation of SLT in the EFL classroom, arises with the need to examine the pedagogical methods and techniques used by teachers in SLT to foster English language skills, as well as students’ motivation to learn. This semi-systematic review examined four databases to provide an overview of the theoretical underpinnings of SLT and current studies with different methodologies, participants, and the efficacy of SLT in the development of EFL learners’ language skills, moti-vation and learning styles. The review provides an updated overview on SLT and its influence on the develop-ment of language skills of EFL learners.